Carnosine Ameliorates Stress-Induced Glucose Metabolism Disorder in Restrained Mice - Bun Tsoi; Rong-Rong He; Dong-Hui Yang; Yi-Fang Li; Xiao-Di Li; Wei-Xi Li; Keiichi Abe; Hiroshi Kurihara (Elsevier, 2011)
Abstract.: Carnosine is a natural dipeptide that has shown multiple benefits in the treatment of various diseases. This study investigated the ameliorative effects of carnosine on glucose metabolism in restraint-stressed mice. Our results showed that restraint stress could significantly influence glucose metabolism, as reflected by lowered glucose tolerance, hepatic and muscle glycogen content, and increased plasma corticosterone concentration in mice. Oral administration of carnosine (150 and 300 mg/kg) not only reverted stress-induced decline in glucose tolerance and glycogen content in liver and muscle, but also reduced plasma corticosterone level. Carnosine has also significantly suppressed mRNA expression of glucose-6-phosphatase, while elevating glycogen synthase 2, glucokinase and glucose transporter 2 expressions in the liver. The obtained results demonstrated the harmful effects induced by restraint stress, while proving that carnosine could ameliorate stress-induced glucose metabolism disturbance. It is presumable that carnosine exerts its anti-stress effects by indirectly affecting the histaminergic neuron system, modulating the stress-activated hypothalamic-pituitary-adrenal axis and improving glucose metabolism through regulation of the enzymes in the glucose metabolic pathways. Keywords:: carnosine, restraint stress, glucose metabolism disorder, corticosterone, gene expression